Effectiveness of simplified predictive intubation difficulty score and thyromental height in head and neck surgeries: an observational study - Selvi,Onur (2020)
Abstract Background and objectives: In this study, we aimed to investigate the predictive value of different airway assessment tools, including parts of the Simplified Predictive Intubation Difficulty Score (SPIDS), the SPIDS itself and the Thyromental Height Test (TMHT), in intubations defined as difficult by the Intubation Difficulty Score (IDS) in a group of patients who have head and neck pathologies. Methods: One hundred fifty-three patients who underwent head and neck surgeries were included in the study. The Modified Mallampati Test (MMT) result, Thyromental Distance (TMD), Ratio of the Height/Thyromental Distance (RHTMD), TMHT, maximum range of head and neck motion and mouth opening were measured. The SPIDSs were calculated, and the IDSs were determined. Results: A total of 25.4% of the patients had difficult intubations. SPIDS scores >10 had 86.27% sensitivity, 71.57% specificity and 91.2% Negative Predictive Value (NPV). The results of the Receiver Operating Curve (ROC) analysis for the airway screening tests and SPIDS revealed that the SPIDS had the highest area under the curve; however, it was statistically similar to other tests, except for the MMT. Conclusions: The current study demonstrates the practical use of the SPIDS in predicting intubation difficulty in patients with head and neck pathologies. The performance of the SPIDS in predicting airway difficulty was found to be as efficient as those of the other tests evaluated in this study. The SPIDS may be considered a comprehensive, detailed tool for predicting airway difficulty.